Mud to bricks: A review of school infrastructure spending and delivery - Carmen Abdoll (Pretoria University Law Press (PULP), 2014)
About the publication Dilapidated public school infrastructure can be found across the country, but the problem is particularly acute in the Eastern Cape where the majority of the so called 'mud schools' are located. On 04 February 2011, following court action on the issue of mud schools, the Legal Resources Centre, acting on behalf of 7 schools and the Centre for Child Law, concluded a landmark settlement with the National Department of Basic Education in which the Department committed to spend R8.2-billion from 1 April 2011 to 1 March 2014 to eradicate mud schools and improve infrastructure of schools throughout South Africa. The Centre for Child Law commissioned Cornerstone Economic Research, to track school infrastructure spending and delivery. The aim of the research was to assess what progress has been made in addressing the issues that brought about the litigation. This study, amongst other things, makes the concerning finding that the Department has woefully underspent the allocated school infrastructure funding for two years running. The target for the number of schools to be built in 2011/2012 and 2012/2013 was 49. However, only 10 schools had been completed at the end of the first year. About the authors: Carmen Abdoll has experience in public sector finance management, budget analysis, and various tax policy issues, including issues related to value-added tax, excise duties and all sub-national taxes. She has also worked on various projects related to the structure of the intergovernmental fiscal system in South Africa. Carmen has a particular interest in policy and services impacting on the lives of orphan children. Conrad Barberton is a development economist, policy researcher and trainer. He has experience in the design of intergovernmental fiscal processes, public sector finance management, budget presentation design and analysis, the costing of policies, strategic planning, monitoring and evaluation, and the design of governance accountability systems. Table of Contents PREFACE ACKNOWLEDGMENTS EXECUTIVE SUMMARY A LIST OF ABBREVIATIONS AND ACRONYMS 1. Introduction Part one: Status of school infrastructure 2. Responsibility for school infrastructure planning 3. Sources of information on school infrastructure 3.1 Number of public ordinary schools 3.2 Number of classrooms in public ordinary schools 4. Backlogs in school infrastructure 4.1 Planning to address backlogs in school infrastructure 4.2 Backlogs in schools and classrooms 4.3 Inappropriate school structures (so-called mud schools) 4.4 Backlogs in basic services 4.5 Backlogs in maintenance Part two: National and provincial funding of school infrastructure 5. Determinants in the demand for school infrastructure 6. National government allocations to school infrastructure 6.1 Education Infrastructure Grant 6.2 School Infrastructure Backlogs Grant 7. Provincial allocations to school infrastructure 7.1 Total spending by provinces on school infrastructure 7.2 Provinces' allocations of own funding to school infrastructure Part three: Performance in the delivery of school infrastructure 8. Performance of the School Infrastructure Backlogs Grant 8.1 Planning related to the grant 8.2 Spending and delivery progress of the SIBG 8.3 Likely timeframes for eradicating inappropriate school structures 9. Performance of the Education Infrastructure Grant 9.1 Planning related to the grant 9.2 Spending and delivery progress of the EIG 10. Concluding points